2021
DOI: 10.1177/10499091211057049
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Palliative and End-of-Life Care in the COVID-19 Pandemic: A Scoping Review

Abstract: Aim: To identify the nature of the evidence reporting hospital-based palliative and end-of-life care during the COVID-19 pandemic. Background: The COVID-19 pandemic has seen an increase in the numbers of seriously ill people being cared for across all health services worldwide. Due to the rapid progression of severe symptoms, the majority of staff working in hospitals and other healthcare centres were providing end-of-life care. Little is known about the level of hospital-based palliative care service provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Although some hospices and PCUs accepted COVID-19-positive patients, most opted not to [ 49 , 50 ]. In addition, hospice and PCU policies that banned visitors made hospice admission unacceptable for many families, as this would result in their loved one dying alone [ 51 ▪ ]. In the city of Palermo, hospice unit bed occupancy dropped from 95 to 40% [ 49 ].…”
Section: Impact Of Covid-related Resource Limitationsmentioning
confidence: 99%
“…Although some hospices and PCUs accepted COVID-19-positive patients, most opted not to [ 49 , 50 ]. In addition, hospice and PCU policies that banned visitors made hospice admission unacceptable for many families, as this would result in their loved one dying alone [ 51 ▪ ]. In the city of Palermo, hospice unit bed occupancy dropped from 95 to 40% [ 49 ].…”
Section: Impact Of Covid-related Resource Limitationsmentioning
confidence: 99%
“…Data suggests our international counterparts have been able to control symptoms in people dying of COVID-19 with greater success ( 17 ), perhaps in part due to increased compliance with consensus guidelines and greater involvement of palliative care expertise. A recent scoping review ( 23 ) on inpatient COVID-19 deaths showed a large increase in palliative care referrals, whose role was similarly to guide goals of care and symptom management. Other authors have also supported the role of early palliative care in patients at high risk of dying from COVID-19 ( 8 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to COVID-19, family care partners utilized hospice services differently ranging from actively refusing home visits and respite care to reduce risk of exposure to increasing telephone support; and emotionally, experienced heightened stress, anxiety, and grief. Heightened stress and anxiety of dementia family care partners during the pandemic has been reported in community 29 and hospice settings. 15 For family care partners of facility patients, particularly, not being able to see their loved ones and receiving regular communication from the facility raised their anxiety and stress levels, which in turn led to family care partners’ reliance on hospice interdisciplinary teams for patient updates and emotional support.…”
Section: Discussionmentioning
confidence: 99%